Are “Accident and Emergency” Specialists Prepared to Tackle: Secondary Hyperkalemic Quadriparesis: A Case Report and Review - Debasish Mahapatra; Vijoy Kumar Jha; Navin Bhati; Annem Anvesh (APIK Journal of Internal Medicine)
Areflexic periodic quadriparesis due to metabolic abnormalities, especially due to hyperkalemia, is relatively less commonly seen and discussed. The presentation is remarkable, and with high degree of suspicion in an appropriate setting, diagnosis is easy. Similarly, treatment with available options at accident and emergency is hugely satisfactory. We present and discuss a case of secondary hyperkalemic quadriparesis in a patient with end-stage renal disease. We intend to discuss pathophysiology of such condition, diagnosis, and management.